COPD Diagnostic Questionnaire (CDQ) for selecting at-risk patients for spirometry: a cross-sectional study in Australian general practice - Stanley, Anthony J (NPJ Prim Care Respir Med, 2014)
BACKGROUND: Using the COPD Diagnostic Questionnaire (CDQ) as a selection tool for spirometry could potentially improve the efficiency and accuracy of chronic obstructive pulmonary disease (COPD) diagnosis in at-risk patients. AIM: To identify an optimal single cut point for the CDQ that divides primary care patients into low or high likelihood of COPD, with the latter group undergoing spirometry. METHODS: Former or current smokers aged 40–85 years with no prior COPD diagnosis were invited to a case-finding appointment with the practice nurse at various general practices in Sydney, Australia. The CDQ was collected and pre- and post-bronchodilator spirometry was performed. Cases with complete CDQ data and spirometry meeting quality standards were analysed (1,054 out of 1,631 patients). CDQ cut points were selected from a receiver operating characteristic (ROC) curve. RESULTS: The area under the ROC curve was 0.713. A cut point of 19.5 had the optimal combination of sensitivity (63%) and specificity (70%) with two-thirds below this cut point. A cut point of 14.5 corresponded to a sensitivity of 91%, specificity of 35% and negative predictive value of 96%, and 31% of patients below this cut point. CONCLUSIONS: The CDQ can be used to select patients at risk of COPD for spirometry using one cut point. We consider two possible cut points. The 19.5 cut point excludes a higher proportion of patients from undergoing spirometry with the trade-off of more false negatives. The 14.5 cut point has a high sensitivity and negative predictive value, includes more potential COPD cases but has a higher rate of false positives.